Investment in training and skills - Imran Tahir (Institute for Fiscal Studies (IFS), 2023)
The UK has seen a significant decline in investment in adult education and training. This chapter analyses how the skills system should be reformed.
Keywords: 330; Education and skills; Government finances and spending; IFS Green Budget 2023; Education; Further education; Human capital; Investment; Skills; Government spending